Regulatory support for the organic market (in the world, EAEU countries, Russia) - V. F. Pivovarov; A. F. Razin; M. I. Ivanova; R. A. Meshcheryakova; O. A. Razin; T. N. Surikhina; N. N. Lebedeva (Овощи России)
The article presents international and national documents providing regulatory support for the organic market. Organic agriculture, as a special direction of agricultural production, requires separate legislative regulation due to the specifics of relations arising in the process of production, sale and marketing of products, the availability of internationally recognized standards and certification procedures. Most of the countries of the world community have their own characteristics of the development of the sector of organic agricultural products, its production, marketing and regulation of these processes, regulatory support of the market for organic products. Organic farming in Russia today can rely on a system of legal regulation of organic production, including international and interstate acts on organic agriculture (JFOAM, FiBL, Codex Alimentarius Commission, regulations of the EAEU, EAEU and CIS), Federal law (93) and national state RF standards, regional laws and programs for the development of organic agriculture, certification organizations. Prior to the approval and implementation of the Federal Law on organic products at the regional level, several regions of the Russian Federation developed their own regulatory documents that allowed their producers to produce organic products. The legal impact on the formation of the organic market occurs not only through laws of direct action, but also through general economic laws, regulations, state programs, local regulations (for example, private standards of organizations), etc. The current procedure for passing certification in foreign countries and for Russian producers of organic products. The factors and conditions that allow to stimulate producers to increase the production of organic products, to pass the required and necessary certification of farms and products, making local products more competitive in comparison with other similar products are identified.